Findus and the Christmas Tomte - Nordqvist, Sven (Findus and Pettson Series, 2018)
A blanket of snow covers Pettson's farm, and Christmas is approaching. Findus, the talking cat, tells Pettson that he is excited about the Yule Tomte visiting and bringing gifts. "oh dear!' thinks Pettson, 'How can I explain that the Yule Tomte may only visit children?' Findus is adamant that the Yule Tomte must visit him, and as Pettson does not want Findus to be disappointed he decides to build a mechanical Yule Tomte to give Findus his gifts. This proves to be a much harder and stranger undertaking than Pettson imagines. Perhaps what Pettson needs is a little bit of Christmas magic..